Risk factors associated with reproductive disorders in dairy cows in Algeria - BOUDELAL, S.; NIAR, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
In Algeria, there is a lack of information about the prevalence of reproductive health disorders in dairy farms. In this light, the aim of the present study was to determine the effect of parity, body condition score (BCS), calving season, calves’ status at delivery and gender of the calf on the prevalence of dystocia, retained fetal membranes(RFM) and metritis under Algerian field conditions. The study took place from October 2016 to April 2019. It was conducted on 449 dairy cows from 22 commercial dairy farms located in Algerian highland regions (Medea, Tiaret and Tissemsilt areas).The prevalence of dystocia, RFM and metritis was 12%, 16.9%, and 11.8%, respectively. Cows with BCS ≤2.75 were the most affected by RMF (Odds ratio [OR] = 3.66). The main risk factors for RMF were calving abnormalities (OR=3.03), calving in warm season (May to October) (OR= 1.85) and the birth of male calves (OR= 1.75) (P<0.05). Stillbirth, dystocia and RFM were identified as potential risk factors for metritis (P<0.05). These findings confirm again the importance of herd management in prevention of these reproductive disorders.